2023
DOI: 10.1126/science.ade5645
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial nerve net in a ctenophore adds insights on the evolution of nervous systems

Abstract: A fundamental breakthrough in neurobiology has been the formulation of the neuron doctrine by Santiago Ramón y Cajal, which stated that the nervous system is composed of discrete cells. Electron microscopy later confirmed the doctrine and allowed the identification of synaptic connections. In this work, we used volume electron microscopy and three-dimensional reconstructions to characterize the nerve net of a ctenophore, a marine invertebrate that belongs to one of the earliest-branching animal lineages. We fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Second, the observed suppression of complex ciliary patterns by MgCl2 indicates the significance of steady state chemical transmission in generating ctenophore behaviors. This experiment is important because of the recently discovered syncytial organization of five ctenophore neurons in the subepithelial nerve net of early developmental stages of Mnemiopsis (Burkhardt et al, 2023). The finding might be interpreted as support for the widespread role of non-synaptic and nonchemical transmission in ctenophores (Dunn, 2023).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Second, the observed suppression of complex ciliary patterns by MgCl2 indicates the significance of steady state chemical transmission in generating ctenophore behaviors. This experiment is important because of the recently discovered syncytial organization of five ctenophore neurons in the subepithelial nerve net of early developmental stages of Mnemiopsis (Burkhardt et al, 2023). The finding might be interpreted as support for the widespread role of non-synaptic and nonchemical transmission in ctenophores (Dunn, 2023).…”
Section: Discussionmentioning
confidence: 74%
“…However, the majority of neurons in ctenophores and external control of cilia activities are likely mediated by chemical transmission. Specifically, distinct ctenophore neural systems can employ well-recognized synapses already detected by electron microscopy (Hernandez-Nicaise, 1991;Burkhardt et al, 2023) and volume-type intercellular transmission (Moroz et al, 2021) mediated by small peptides, nitric oxide and, perhaps, additional low molecular weight messengers to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of VWYa in SNNs of both B. mikado and V. multiformis suggests a conserved VWYa-mediated function of the SNN among ctenophore species [ 13 ]. Recently, Burkhardt et al (2023) [ 12 ] reported that neurons in the SNNs of M. leidyi larvae form a continuous plasma membrane, resulting in a syncytium without synaptic connections in this network. While it remains uncertain whether other ctenophore species have similar syncytial SNNs, this finding suggests that the pervasive neuropeptide transmission systems in metazoans are uniquely derived in ctenophores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, key transcription factors required for mesodermal specification and muscle differentiation such as twist, NK2.1, par3/7 , and myoD appear to be absent [ 8 , 9 ]. The paucity of distinct neuron-related markers in ctenophores and the presence of unique neural traits such as subepithelial syncytial neural architecture [ 12 ] have been interpreted as evidence that the ctenophore nervous system was acquired independently from those of cnidarian and bilaterian lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Recognisable nervous systems exist in ctenophores and parahoxozoans, although neural cell structure and composition differs markedly between representatives of these lineages (Burkhardt and Jékely, 2021;Moroz et al, 2021;Moroz and Romanova, 2022;Burkhardt et al, 2023). Sponges have cell types that co-express proteins comprising macromolecular complexes in ctenophore and parahoxozoan synapses, and regulatory factors that have strong proneural activity in bilaterians (Sakarya et al, 2007;Richards et al, 2008;Conaco et al, 2012;Wong et al, 2019;Musser et al, 2021).…”
Section: An Ancient Role For Monoamine Signalling In Metazoan Holobiontsmentioning
confidence: 99%